The Influence Of Organizational Justice And Organizational Commitment On Turnover Intention Mediated By Employee Engagement at PT. Perkebulan Nusantara IV Medan - Muhammad Fauzan, Azhmy; Chairunnisa, T. Lyza Tahura; Azhari, Muhammad (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
This research aims to determine the partial effect of organizational justice and organizational commitment on employee engagement. To determine the partial influence of organizational justice, organizational commitment and employee engagement on turnover intention. To determine the effect of organizational justice and organizational commitment on turnover intention through employee engagement at PT. Perkebunan Nusantara IV Medan. The total population in this study was 119 people and all of them were sampled using saturated sampling. The analysis technique used is path analysis. The results of the study indicate that organizational justice has a positive and significant effect on employee engagement, organizational commitment does not have a significant effect on employee engagement, organizational justice does not have a significant effect on turnover intention, organizational commitment does not have a significant effect on turnover intention, employee engagement has a positive and significant effect on turnover intention, employee engagement significantly mediates the effect of organizational justice on turnover intention and employee engagement does not significantly mediate the effect of organizational commitment on turnover intention.